2005
DOI: 10.1089/apc.2005.19.366
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Treatment Considerations in Latino Patients

Abstract: Latinos in the United States have been disproportionately affected by HIV, with a higher rate of infection, later diagnosis, and a higher death rate than Caucasians. Complicating the issue is that "Latino" is a broad term that encompasses diverse ethnic and racial groups, requiring a targeted approach to prevention and management of HIV infection. This article explores the demographics of HIV infection among Latinos in the United States, discusses cultural beliefs among Latinos that have an impact on preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Hispanics comprised approximately 14% of the total US population (including Puerto Rico) in (U.S. Census Bureau, 2004), yet they accounted for over 20% of the total reported AIDS cases that same year (Centers for Disease Control and Prevention [CDC], 2004b). In addition to having a disproportionately high rate of HIV/AIDS diagnoses-an estimated 39 cases per 100,000 population (CDC, 2005)-Hispanics have experienced higher rates of delayed HIV diagnoses and exhibited more AIDS-defining conditions at time of diagnosis than non-Hispanic Whites (Campo, Alvarez, Santos, & Latorre, 2005;CDC, 2003b). Further, HIV disease is ranked as the third leading cause of death among Disclaimer: The findings and conclusions in this report are those of the authors and do not necessarily represent the views of the U.S. Centers for Disease Control and Prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Hispanics comprised approximately 14% of the total US population (including Puerto Rico) in (U.S. Census Bureau, 2004), yet they accounted for over 20% of the total reported AIDS cases that same year (Centers for Disease Control and Prevention [CDC], 2004b). In addition to having a disproportionately high rate of HIV/AIDS diagnoses-an estimated 39 cases per 100,000 population (CDC, 2005)-Hispanics have experienced higher rates of delayed HIV diagnoses and exhibited more AIDS-defining conditions at time of diagnosis than non-Hispanic Whites (Campo, Alvarez, Santos, & Latorre, 2005;CDC, 2003b). Further, HIV disease is ranked as the third leading cause of death among Disclaimer: The findings and conclusions in this report are those of the authors and do not necessarily represent the views of the U.S. Centers for Disease Control and Prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have either found no association between race/ethnicity and condom use among women or less unprotected sex among African American women compared to their White counterparts (Merchant et al, 2006; Parks, Hsieh, Collins, Levonyan-Radloff, & King, 2009; Paterno & Jordan, 2012; Reece et al, 2010). Studies of men suggest that Black and Latino men are at disproportionately high risk for HIV infection (Centers for Disease Control and Prevention, 2013) and for disparities in access to HIV medical care (Campo et al, 2005). However, some of this increased risk may be attributable to coincident demographic factors such as limitations in social mobility, economic disenfranchisement, and cultural marginalization (El-Sadr et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The 2013 rate of HIV infection was also disproportionately high among both African American men (105.7 per 100,000) and Latino men (41.8 per 100,000) as compared to White men (13.8 per 100,000) (Centers for Disease Control and Prevention, 2013). When Black or Latino patients are diagnosed with HIV, they are more likely to experience delayed access to care (Campo, Alvarez, Santos, & Latorre, 2005). In addition to racial/ethnic minorities, people most at risk for HIV infection are those with limited social mobility, economic disenfranchisement, and cultural marginalization (El-Sadr, Mayer, & Hodder, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to remember, however, that many Latino patients present in late stages of HIV, and initiation of ARV therapy should not be unduly delayed because of adherence concerns. For patients who are unlikely to reach 100% adherence, agents with high barriers to resistance and good kinetic profiles are preferable [23]. Although protease inhibitors (PIs) are usually preferred over nonnucleoside reverse transcriptase inhibitors (NNRTIs) in patients with adherence issues, other factors, such as the availability of refrigeration (especially for migrant workers), must be considered and may influence the choice of drug.…”
Section: Adherencementioning
confidence: 99%